2016
DOI: 10.1128/mcb.00770-15
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Histone Expression or a Defect in Chromatin Assembly Induces Respiration

Abstract: Regulation of mitochondrial biogenesis and respiration is a complex process that involves several signaling pathways and transcription factors as well as communication between the nuclear and mitochondrial genomes. Here we show that decreased expression of histones or a defect in nucleosome assembly in the yeast Saccharomyces cerevisiae results in increased mitochondrial DNA (mtDNA) copy numbers, oxygen consumption, ATP synthesis, and expression of genes encoding enzymes of the tricarboxylic acid (TCA) cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 84 publications
4
31
0
Order By: Relevance
“…Denatured proteins were separated on 10 or 12% denaturing polyacrylamide gels. Western blotting was performed as described previously (82). Western blots were quantified using NIH ImageJ software (W. siRNA Transfections-Human AMPK␣1/2 (sc-45312), ACCA (sc-40312), LKB1 (sc-35816), and non-silencing (sc-37007) siRNAs were obtained from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…Denatured proteins were separated on 10 or 12% denaturing polyacrylamide gels. Western blotting was performed as described previously (82). Western blots were quantified using NIH ImageJ software (W. siRNA Transfections-Human AMPK␣1/2 (sc-45312), ACCA (sc-40312), LKB1 (sc-35816), and non-silencing (sc-37007) siRNAs were obtained from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work has shown that altered chromatin structure in S. cerevisiae induces transcription of HAP4 and respiration (36). On the basis of nucleosomal chromatin architecture, yeast genes can be classified into two broad groups: growth genes and stress genes (37).…”
mentioning
confidence: 99%
“…The respiratory genes in S. cerevisiae belong to the stress gene category unlike respiratory genes in higher eukaryotes (38,39). Altered chromatin structure in S. cerevisiae makes promotors of respiratory genes more accessible to transcription factors and allows increased expression of respiratory genes and transition from fermentation to respiration (36). The increased transcription of respiratory genes and induction of respiration require a product of mitochondrial carbon metabolism (36).…”
mentioning
confidence: 99%
“…Mitochondrial biosynthesis up-regulates both mitochondrial respiratory chain enzymes and mitochondrial antioxidant factors (such as Mn-SOD and GSH-Px) (30,31). Mitochondrial biosynthesis depends on the expression of mitochondrial genome (mtDNA) and nuclear genome (nDNA), and mtDNA is the main target of ROS-mediated damage (32). PGC-1α plays a central role in the regulation of mitochondrial production.…”
Section: Discussionmentioning
confidence: 99%